Prevalence of Glaucoma in Patients With Vitiligo - Dertlioglu, Selma Bakar; Oguz, Halit; Cicek, Demet; Yucel, Hatice (Quadrant Healthcom Inc, 2016)
Vitiligo is an acquired idiopathic disease characterized by depigmented maculae and melanocytic destruction. We determined the prevalence of glaucoma in 49 patients who had presented to the dermatology polyclinic with vitiligo and compared that with the prevalence of glaucoma in 20 age- and sex-matched healthy controls. All patients were given an ophthalmologic examination to identify any glaucomatous changes. In the vitiligo group, 9 patients (18.4%) were found to have signs of normal-tension glaucoma (NTG), while there were no signs of NTG in the control group. This difference between the 2 groups was statistically significant (P=.04). Because glaucoma can cause permanent vision loss when left untreated, its greater prevalence among patients with vitiligo suggests that these patients should be carefully monitored.
Keywords: Low-Tension Glaucoma; Destruction